UPAYA MENINGKATKAN MINAT BELAJAR IPAS MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWERPOINT ANIMASI BERGERAK PADA SISWA KELAS IV SD MUHAMMADIYAH AMBARBINANGUN KALIPAKIS TIRTONIRMOLO KASIHAN BANTUL - Lailatul Mubarokah; Beny Dwi Lukitoaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the increase in learning interest in grade IV in science lessons with interactive learning media based on animated powerpoint at Muhammadiyah Ambarbinangun Elementary School. Classroom Action Research (PTK) is a research method that is carried out in two cycles with four stages in each cycle, namely planning, implementation, observation, and reflection. The subject of this study is grade IV students of Muhammadiyah Ambarbinangun Elementary School which consists of 25 students. The data collection technique of this research is by observation, questionnaire and documentation. The analysis used in this study is descriptive analysis both qualitatively and quantitatively. The results of this study show that there is an increase in teacher activity in social studies learning, namely in the first cycle it reached 72.22% and the second cycle 92.59%, there was an increase in student activity in social studies learning, namely in the first cycle it reached 61.54% and in the second cycle 82.59%, there was an increase in student learning interest, namely in the first cycle it reached 44.00% and in the cycle 92.00%. So it can be concluded that using interactive learning media based on powerpoint moving animation can increase teacher activities, student activities and student learning interests in social studies subjects in grade IV of Muhammadiyah Ambarbinangun Elementary School.